Multidrug resistant miliary tuberculosis during infliximab therapy despite tuberculosis screening. (29th May 2013) - Gin, Alexander; Dolianitis, Con
Abstract We describe an unusual case of multidrug‐resistant miliary tuberculosis diagnosed 9 months after the commencement of infliximab treatment for psoriasis despite negative pretreatment tuberculosis screening, including chest X‐ray and interferon‐gamma release assay. After 4 months' treatment with amikacin, ethambutol, pyrazinamide and moxifloxacin, infliximab was restarted with concomitant anti‐TB medications. No recurrence of tuberculosis has been detected 12 months after recommencing infliximab.